2005
DOI: 10.1038/sj.bjc.6602745
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific occurrence of nonmelanoma skin cancers in patients with cutaneous melanoma

Abstract: In a registry-based case -control study, we compared the site-specific occurrence of nonmelanoma (keratinocytic) skin cancers among patients with cutaneous melanoma cases (cases, n ¼ 3774) and solid tumours (controls, n ¼ 349 923), respectively. Overall, patients with melanoma were almost five-fold more likely to develop keratinocytic cancers compared with solid tumour controls (adjusted OR 4.7, 95% CI 4.1 -5.3), but the risks varied depending upon the site of melanoma. Whereas patients with melanoma of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Eight percent of melanoma patients develop a secondary melanoma within 2 years of their initial diagnosis [ 8 ]. Melanoma patients also have increased risk of developing other NMSC [ 9 ]: 35% of the patients with lentigo maligna melanomas develop another cutaneous malignancy within 5 years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eight percent of melanoma patients develop a secondary melanoma within 2 years of their initial diagnosis [ 8 ]. Melanoma patients also have increased risk of developing other NMSC [ 9 ]: 35% of the patients with lentigo maligna melanomas develop another cutaneous malignancy within 5 years [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other cancers, BCC has a complex relationship with sunlight, with many lesions developing on areas that are not frequently exposed to the sun, an age-related plateau in incidence, and a significant relationship between recreational exposure and risk [ 35 ]. On the other hand, the incidence of SCC monotonically increases in the presence of sunlight [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standard measure, sun exposure has generally been classified as intermittent or chronic, and its effects can be considered short-term or cumulative. Intermittent sun exposure appears to be the most important risk factor for melanoma [16,17]. Analytical epidemiological studies have shown the role of intermittent exposure to the sun and are shown schematically in the following table (with odds ratios [OR] of 1.6 to 1.7)…”
Section: Sex Menmentioning
confidence: 99%